2011
DOI: 10.1155/2011/534391
|View full text |Cite
|
Sign up to set email alerts
|

On a Result of Levin and Stečkin

Abstract: The following inequality for0<p<1andan≥0originates from a study of Hardy, Littlewood, and Pólya:∑n=1∞((1/n)∑k=n∞ak)p≥cp∑n=1∞anp. Levin and Stečkin proved the previous inequality with the best constantcp=(p/(1-p))pfor0<p≤1/3. In this paper, we extend the result of Levin and Stečkin to0<p≤0.346.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Recently, the author [14] has extended the result of Levin and Stečkin to hold for 0 < p 0.346. Inequalities of type (1.5) with more general weights are also studied in [14], among which the following one for 0 < p < 1, α 1:…”
Section: ) Occursmentioning
confidence: 92%
“…Recently, the author [14] has extended the result of Levin and Stečkin to hold for 0 < p 0.346. Inequalities of type (1.5) with more general weights are also studied in [14], among which the following one for 0 < p < 1, α 1:…”
Section: ) Occursmentioning
confidence: 92%
“…The equivalence of the above two inequalities can be easily established following the discussions in [8,Sect. 1].…”
Section: Introductionmentioning
confidence: 98%
“…(1.4) It is noted in [12] that the constant p p in (1.4) may not be best possible and the best constant for 0 < p ≤ 1/3 was shown by Levin and Stečkin [13, Theorem 61] to be indeed (p/(1p)) p . In [8], it is shown that the constant (p/(1p)) p stays best possible for all 0 < p ≤ 0.346. It is further shown in [11] that the constant (p/(1p)) p is best possible when p = 0.35.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations